Characterizing the gastrointestinal tract microbiota of dairy calves - Dias, Juliana (2017)
At birth, calves display an underdeveloped gastrointestinal tract (GIT) whose maturation is strictly related to microbiota colonization. However, little is known about the factors that affect the establishment of archaeal, bacterial and fungal communities in the GIT of calves, as well as the changes in their structure and abundance during calf development into a functional ruminant. To address these gaps in knowledge, this work employed next-generation sequencing to characterize the GIT microbiota of Holstein- Gyr crossbred dairy calves across pre-weaning development. The first study aimed to assess changes on the rumen archaeal, bacterial and fungal communities of crossbred dairy calves (n=45) across pre-weaning development (7, 28, 49, 63 days) on two different diets (M: only raw milk at 10% of body weight at birth (BW) and MC: raw milk (10% BW) plus starter concentrate ad libitum). In the second study, we characterized changes in the bacterial communities across GIT regions (rumen, jejunum, cecum and colon) of MC-fed calves (n=17) at 7, 28, 49, 63 days of age. The results of first study revealed that archaeal, bacterial and fungal communities co-occur in the rumen since early calf development but are impacted differently by pre-weaning diet and age. The inclusion of starter concentrate in the calf diet significantly affected rumen bacterial community by promoting increases of genera, direct and indirectly, related to degradation of readily fermentable carbohydrates (i.e. Megasphaera, Sharpea and Succinivribrio) and depressing those reliant on milk nutrients like lactose (i.e. Lactobacillus, Bacteroides and Parabacteroides). These bacterial changes resulted in apparent diet-driven archaeal differences due to altered fermentation patterns and availability of hydrogen in the rumen that favoured the colonization of members from genus Methanosphaera instead of Methanobrevibacter. No such differences were found for fungi community represented by members from genus Caecomyces and family Neocallimastigaceae, likely due to high inter-animal variation and low fibre content of concentrate used our study. Altogether, this study showed that manipulation of the microbiota in the developing rumen is possible through dietary intervention. Our results may be useful in designing strategies to promote colonization of target communities (i.e. butyrate- producers and lactate-utilizing) linked to functional development of the calf. In regards to second study, bacterial communities in the calf GIT differ qualitatively and quantitatively among compartments and respond differently to age advance that encompass the GIT development (i.e. rumen) and progressive replacement of milk- based to grain-diet (i.e. increase of starter concentrate intake). In the rumen, bacterial community was composed majority by members from genera Prevotella, Butyrivibrio and Ruminococcus whose abundance increased proportionally with age possibly due greater availability of readily fermentable carbohydrates in the rumen. Members from genus Lactobacillus were overrepresented in the jejunum but their predominance was replaced by members from Clostridiaceae family in older calves. The cecum and colon displayed similar abundance at taxa level and the abundance of genera Blautia, Paraprevotella, Prevotella, Phascolarctobacterium and Succiniclasticum increased significantly with age. In summary, our results showed that although there are bacterial communities “common” to distinct regions, a closer look at their structure, abundance and dynamic reveals marked segregation and ecological succession in the calf GIT. Our study adds new insights into bacterial colonization across GIT of pre-ruminant that may be considered in formulating strategies to promote the colonization of target communities aiming improve health (i.e. bacteria with probiotic capability) and performance of dairy calves in the pre-weaning period.